Utility, Safety, and Accuracy of Intraoperative Angiography in the Surgical Treatment of Aneurysms and Arteriovenous Malformations - Vitaz, Todd W. (American Society of Neuroradiology, 1999)

(untitled) (AJNR Am J Neuroradiol)
BACKGROUND AND PURPOSE: The role of intraoperative angiography in the treatment of neurovascular lesions has remained extremely controversial. We retrospectively reviewed the utility, safety, and accuracy of intraoperative angiography to ascertain its effect on the treatment of patients with neurovascular lesions. METHODS: We reviewed the results of intraoperative angiography in 91 patients treated surgically for intracranial aneurysms and in 98 patients treated surgically for arteriovenous malformations (AVMs). All treatments were completed at two major teaching hospitals between October 1987 and March 1995. RESULTS: The initial angiographic findings caused the surgical procedure to be modified in 24 (26%) of the patients with aneurysms and in 28 (29%) of the patients with AVMs. Analysis of the final angiographic sequence showed residual lesions in nine (10%) of the aneurysm cases and in eight (8%) of the AVM cases. The imperfect angiographic results were deemed acceptable because there was either evidence of collateral flow when the parent vessel was occluded or the risk of further surgical modification was considered more dangerous than the abnormality itself. Seven patients suffered complications, of which only one had permanent neurologic sequelae: a CNS complication rate of 0.5%. Comparison of the intraoperative angiographic findings with those of postoperative studies revealed four false-negative results (5.2%). CONCLUSION: Intraoperative angiography is an important component in the treatment of patients with intracranial vascular lesions. It is effective and can be carried out with low risk in this patient population.